2013
DOI: 10.1155/2013/906726
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Green Propolis Suppresses the Hypoxia-Induced Neuroinflammatory Responses by Inhibiting NF-κB Activation in Microglia

Abstract: Hypoxia has been recently proposed as a neuroinflammatogen, which drives microglia to produce proinflammatory cytokines, including interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), and IL-6. Considering the fact that propolis has hepatoprotective, antitumor, antioxidative, and anti-inflammatory effects, propolis may have protective effects against the hypoxia-induced neuroinflammatory responses. In this study, propolis (50 μg/mL) was found to significantly inhibit the hypoxia-induced cytotoxicity and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 48 publications
2
54
0
Order By: Relevance
“…These observations suggest that microglia in the aged brain are primed and over-reacted to systemic challenges [29][30][31][32][33]. More recently, the mean level of IL-1β secreted by primary cultured microglia prepared from the aged brains is significantly higher than that from the young brains [12,29,34]. These observations further support our proposed concept of "microglia-aging" [2,35] (Figure 1).…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations
“…These observations suggest that microglia in the aged brain are primed and over-reacted to systemic challenges [29][30][31][32][33]. More recently, the mean level of IL-1β secreted by primary cultured microglia prepared from the aged brains is significantly higher than that from the young brains [12,29,34]. These observations further support our proposed concept of "microglia-aging" [2,35] (Figure 1).…”
Section: Introductionsupporting
confidence: 77%
“…We have previous found that excessive production of ROS due to the increased oxidative mtDNA damages in microglia is responsible for exaggerated neuroinflammatory responses in the aged animals after treatment with LPS, because the increased intracellular ROS level activates NF-κB signaling pathway which regulates the expression of several proinflammatory mediators [2]. Hypoxia can drive microglia to generate ROS [3][4][5][6], and we have recently found that hypoxia activates NF-κB signaling pathway to induce exaggerated inflammatory responses by microglia [12] (Figure 1). The brain is highly vulnerable to hypoxic stress due to its high oxygen requirement and therefore, low oxygen availability at high altitudes results in cognitive impairments [47].…”
Section: Acceleration Of "Microglia-aging" During Hypoxiamentioning
confidence: 99%
See 3 more Smart Citations